RESENHA DO LIVRO EDITING AND MONTAGE IN INTERNATIONAL FILM AND VIDEO: THEORY AND TECHNIQUE - Pedrosa, Joan Marimon (TROPOS: COMUNICAÇÃO, SOCIEDADE E CULTURA (ISSN: 2358-212X), 2017)
MORANTE, Luís Fernando Morales Morantes. Editing and Montage in international film and video: theory And technique. Oxford: Focal Press, 2017.